Incentive pay for non-executive directors: The direct and interaction effects on firm performance - Adithipyangkul, Pattarin; Leung, T. (Springer New York LLC, 2017)
© 2017 Springer Science+Business Media, LLC To improve corporate governance and firm performance, institutional investors and influential activists in the US recommend the use of incentive pay for non-executive directors. Policy makers in the UK and Australia, however, recommend against it. Motivated by stark contrast in the recommendations from these Anglo-Saxon countries, this paper investigates the impacts of incentive pay for non-executive directors on firm performance. The findings based on data from 178 listed Australian companies support both recommendations. Firm performance tends to be better when no incentive or high-power incentives are offered to non-executive directors than when low-power incentives are offered. This paper also investigates how incentive pay interacts with monitoring by large shareholders and debtholders to influence firm performance. This paper shows that large shareholder monitoring interacts negatively while debtholder monitoring interacts positively with incentive pay for non-executive directors to affect firm performance. Overall, the findings suggest that governance mechanisms recommended by agency theorists such as performance-contingent pay and monitoring can backfire if they are not designed properly. Both the direct and interaction effects should be considered when practitioners design corporate governance systems.